2019
DOI: 10.1111/jppi.12320
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Organizational Supports on the Person‐Centered Health of People With Intellectual and Developmental Disabilities

Abstract: People with intellectual and developmental disabilities (IDD) have significantly poorer health than the general population. A key threat to health programs for people with IDD is commitment from stakeholders, especially service organizations. The aim of this study was to explore the role disability service organizations play in promoting the best possible physical and mental health of people with IDD. To do so, this study analyzed secondary Personal Outcome Measures® data from 1,341 people with IDD in the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Beach et al (2020) found that the cost to treat elder community-based adults with disability rose when those adults and their caregivers reported unmet needs. Similarly, Friedman et al (2020), found that individuals with intellectual and developmental disability were 3.52 times more likely to have the best possible health outcomes when organizational care from support services understood the individual person's definition of “best possible health”, indicating person centered care was taking place.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Beach et al (2020) found that the cost to treat elder community-based adults with disability rose when those adults and their caregivers reported unmet needs. Similarly, Friedman et al (2020), found that individuals with intellectual and developmental disability were 3.52 times more likely to have the best possible health outcomes when organizational care from support services understood the individual person's definition of “best possible health”, indicating person centered care was taking place.…”
Section: Discussionmentioning
confidence: 97%
“…These approaches focus on ensuring the individual has informed choice, which leads to a supported decision that increases quality of life and improves outcomes. Friedman et al (2020) found that individuals who had "the best organization supports" were 3.36 times more likely to select health services in consultation with healthcare professionals indicating the decision-making process was supported.…”
Section: Discussionmentioning
confidence: 99%
“…En ese caso existen hasta trece veces más posibilidades que las PCED muestren mejoras en su salud. Esos apoyos es más fácil conseguirlos en instituciones destinadas a ellos, donde se puede atender a cada uno según sus necesidades (Friedman et al, 2020). De hecho, se ha observado que estos problemas son menores si las personas están tratadas en un centro que si están atendidas en casa (Folch-Mas et al, 2017).…”
Section: El Trabajo Y La Saludunclassified